The Identification of Slurs and Swear Words in Bronte Sisters’ Novels - Citra Suryanovika; Irma Manda Negara (Bina Nusantara University, 2019)
This research aimed at identifying the categories of slurs, presenting how swear words expressed in male or female characters of Bronte sisters’ novels, and examining the social status scale in presenting slurs. The research was a qualitative content analysis of which process was categorizing, comparing, and concluding. The researchers employed MAXQDA 2018.1 (the data analysis tool) for analyzing the samples of five female and male main characters of the novel of Emily Bronte (Wuthering Heights), Charlotte Bronte (Jane Eyre), and Anne Bronte (The Tenant of Wildfell Hall). The research has shown three out of nine Thurlow’s pejorative items (social personality, phallocentric, and sexist), the possible formation of social personality slurs, the identification of swear words for showing speakers’ emotional states, and the influence of social status scale on the expression of slurs. It proves that slurs and swear words are used to deliver a derogatory attitude. The sexist slurs are not only delivered from male characters to female characters, but it is also found in Catherine Earnshaw targeting Nelly although they have similar gender background (female). Slurs are found in the characters from both high and low social rank since the plot develops the relationship amongst the characters. One unexpected finding is the different swear words between the characters. Swear words found in the novel are not only dominated by the word devil, damn, or by hell, but also the word deuce and humbug. The varied swear words proves that the male characters do not dominantly produce swear words, but also euphemistic expression.